The motives for Chinese and Western countries' sovereign lending to Africa - Eckhardt Bode (Kiel Institute for the World Economy (IfW Kiel), 2024)
This paper is one of the first to show systematically that the motives for sovereign lending to African countries differed considerably between China and Western countries during the last two decades. While Chinese lending mainly served its own economic or geopolitical objectives, which is well-known from the existing literature, Western countries' lending also pursued objectives that appear to be at odds with their self-interests but whose precise nature is not yet well-understood. While China lent to African countries with richer resources, lower risk of default and higher willingness to pay for credit, Western countries lent preferably to less resource-rich and more indebted African countries. Using a new, dataset on loans from China, Western countries and multilateral organizations to African countries, I empirically examine a broad variety of potential motives, aim at separating the motives pursued by the national governments from those pursued by their lending agencies, and employ an estimation strategy with increasingly complex fixed effects that yields additional interesting insights into the specificities of the motives.
Keywords: F21; F34; F35; F55; H63; 330; Sovereign lending; Economic motives; Geopolitical motives; Africa; China; Western countries